2010
DOI: 10.1371/journal.pone.0012298
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Urodynamics of Rat

Abstract: In humans, the storage and voiding functions of the urinary bladder have a characteristic diurnal variation, with increased voiding during the day and urine storage during the night. However, in animal models, the daily functional differences in urodynamics have not been well-studied. The goal of this study was to identify key urodynamic parameters that vary between day and night. Rats were chronically instrumented with an intravesical catheter, and bladder pressure, voided volumes, and micturition frequency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
7
44
0
Order By: Relevance
“…It has been reported that micturition shows a diurnal change in rodents as well as in humans 8,22,28,29 , although the day-night change is inverted because of the difference in diurnal versus nocturnal habits. However, it is unknown whether these changes are induced by an endogenous oscillator or only by a reflection of external light-dark changes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that micturition shows a diurnal change in rodents as well as in humans 8,22,28,29 , although the day-night change is inverted because of the difference in diurnal versus nocturnal habits. However, it is unknown whether these changes are induced by an endogenous oscillator or only by a reflection of external light-dark changes.…”
Section: Resultsmentioning
confidence: 99%
“…A voiding contraction was defined as an increase in bladder pressure that resulted in urine loss. Peak micturation pressure was the maximum pressure during micturation as observed in CMGs (24).…”
Section: Methodsmentioning
confidence: 93%
“…By 14 days postinjury, residual urine volumes had stabilized at a mean of ϳ2.94 ml (range, 0.15 ml to 10.6 ml), which is approximately twice the bladder capacity of spinal cord-intact rats (15). Notably, mean residual urine volumes in SCI rats remain stable at ϳ2.5 to 3.0 ml for at least an additional 2 weeks (i.e., up to 4 weeks post-SCI; data not shown).…”
Section: Sci Rats Develop a Neurogenic Bladder Phenotype Characterizementioning
confidence: 92%